Effects of Vitamin D Supplementation on Renin and Aldosterone Concentrations in Patients with Advanced Heart Failure: The EVITA Trial - Armin Zittermann; Jana B. Ernst; Sylvana Prokop; Uwe Fuchs; Jens Dreier; Joachim Kuhn; Cornelius Knabbe; Jochen Börgermann; Heiner K. Berthold; Stefan Pilz; Ioanna Gouni-Berthold; Jan F. Gummert (International Journal of Endocrinology)
Objective. 1,25-Dihydroxyvitamin D (1,25([OH]2D) is considered to be a negative endogenous regulator of the renin-angiotensin-aldosterone system (RAAS), but the effect of vitamin D supplementation on the RAAS is inconclusive. Design. In this prespecified secondary analysis of a randomized controlled trial, we assessed in 165 patients with heart failure (vitamin D group: n=83; placebo group: n=82) the effect of three years of vitamin D supplementation with 4000 IU daily on parameters of the RAAS (renin and aldosterone) and on circulating 1,25(OH)2D, plasma phosphate, and fibroblast growth factor (FGF)-23. We assessed age- and baseline-adjusted between-group differences at study termination. Results. Almost all patients were under treatment with beta-blockers, inhibitors of the RAAS, and diuretics. Initially, the frequency of concentrations above the laboratory-specific reference range (renin: >23.9 mIU/L; aldosterone: >232 ng/L) in the vitamin D and placebo group was 87.7% and 92.7%, respectively (renin), and 24.1% and 32.5%, respectively (aldosterone). Vitamin D increased adjusted 1,25(OH)2D concentrations significantly (mean treatment effect and 95% CI: 18.3 pmol/L,7.3 to 29.3 pmol/L; P<0.001) but had no significant effects on phosphate (0.18 mmol/L, −0.00 to 0.35 mmol/L; P=0.051), FGF-23 (685 RU/mL, −213 to 1585 RU/mL; P=0.134), renin (312 mIU/L, −279 to 902 ng/L; P=0.298), or aldosterone (−0.19 ng/L, −5.09 to 4.70 ng/L; P=0.938). Vitamin D supplementation was, however, associated with an increase in renin concentrations in the subgroup with baseline 25-hydroxyvitamin D below 30 nmol/L (n=67; 1365 mIU/, 343 to 2386 mIU/L; P=0.010). Conclusions. In patients with advanced heart failure treated according to evidence-based guidelines, vitamin D supplementation did not significantly influence parameters of the RAAS in the entire study cohort but was associated with an increase in plasma renin concentrations in the subgroup with low baseline 25-hydroxyvitamin D concentrations.